Effective Strategies of Learning Vocabulary - Ismoilova Mamlakat Qurbonovna; Nuftillayev Bekzod Ubaydillo o’g’li (Genius Journals, 2021)
Vocabulary knowledge is critical to reading comprehension, it is important that those working with young readers help foster their development of a large word bank‖ and effective vocabulary learning strategies. There are several effective explicit (intentional, planned instruction) and implicit (spontaneous instruction as a child comes to new words in a text) strategies that adults can employ with readers of any age. One of the most effective methods of helping children learn new vocabulary words is to teach unfamiliar words used in a text prior to the reading experience.
Keywords: Vocabulary; reading comprehension; unfamiliar words; reading experience